Introduction to Dossier. Dispossession, Social Segregation of Space and Territories in Resistance in Latin America - Ivette Vallejo; Giannina Zamora; William Sacher (Íconos)
Accumulation due to dispossession in Latin America has intensified in the last decade, creating new areas of sacrifice for the installation of hydrocarbon, energy-mining, monoculture, agroindustry and biofuel projects. These projects have brought with them an assemblage of roads and infrastructures to locate, extract, and transport commodities to the global market. While the national and international elites obtain the economic benefits of said projects, new forms of dispossession of territories and common goods in the region are renewed. This article offers a conceptual approach of incarnated dispossessions. It also shows a panorama of the forms of resistance of local communities that form defense fronts and create organizations, with women who face the precarization of their livelihoods taking on strong protagonist role. The contemporary resistances and re-existences are anchored to the historicity of the regional struggles, strengthening or recreating identities.